Efek Suhu Aktivasi terhadap Struktur Mikro Material Karbon Aktif Pelepah Enceng Gondok untuk Aplikasi Elektroda Superkapasitor - Heindrich Taunaumang; Ishak Pawarangan; Farly Tumimomor (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
Supercapacitor electrode material bassed on Pelepah Enceng Gondok Activated Carbon (KAPEG have been developed for increasing the performance of the supercapacitor application. The activated carbon surface structure and its properties strongly depend on the pyrolysis temperature and the type of activation methods. The bamboo carbon has been fabricated using pyrolysis method. The KAPEG was produced using chemical activation with H3PO4 as activation agent with variation of temperature activation 750oc have been carried out. Characterization of the surface structure (functional groups vibration) of bamboo carbon (CB) pyrolysis and the Pelepah enceng Gonddok activated carbon (KAPEG) were carried out using FTIR. The aim of this research is  to identify the functional groups vibration. he FTIR rssults shows absorption peeaks of functional groups of -OH, C=O, C-O, C-H and C-C vibration. The increasing of wavenumber of absorption peaks of functional groups -OH stretching, C=O stretching and C-H indicate that the functional groups bond for KAPEG samples becomes more stronger than for KPEG sample. The conclusion of this research are: the increasing of wavenumber of absorption peaks for functional groups indicates of more stronger of functional groups bond.